Applicability of plastic mulch and conservation strip tillage for potato production in Bangladesh - Md. Abdul Kader; Ferdous Hossain Khan; Shibli Sadik Tulip; Md. Abid Hossain Mridha; Arif Jewel (Universitas Sebelas Maret, 2021)
Application of plastic mulches in potato production is rarely used by farmers in Bangladesh although it has a good prospect for saving irrigation water, weed control, maintaining tuber quality, and increasing yield. A study was conducted in experimental farm at Rural Development Academy (RDA), Bogura, Bangladesh to evaluate the precision of irrigation water for potato production using different colored plastic mulches i.e, black and blue in combination with conservation strip tillage and control (no-mulch). Four different treatments were prepared where some of the phenological characteristics of plants as well as yield of potato were compared among treatments by applying the same amount of irrigation water. The results showed that treatment with black plastic mulch had the highest tuber growth as well as yield of 25.1 t ha-1 compared to other treatments while other treatments such as blue plastic mulch, control, and strip tillage had a yield of 16.37, 13.75, and 15.75 t ha-1, respectively. Potato plants having black plastic mulch took less time to mature in comparison to other treatments. Black plastic mulch restricts soil moisture evaporation and keeps the soil warm. In conclusion, potato production with various mulches has a great scope in a semi-arid region like Bangladesh and present experimental results will help to improve the understanding of potato growers for adopting best mulch management practices.Nikmati pengalaman bermain slot zeus, grafis epik dan fitur bonus hadir untuk meningkatkan peluang kemenangan.